Mozambique : Capacity Building for Integrated Coastal Zone Management - Mohan, P.C. (World Bank, Washington, DC, 2012)
The coastal zone of Eastern Africa includes the coastal lowlands from Sudan to South Africa, the nearshore islands off the coasts of Tanzania and Mozambique, and the oceanic islands of Madagascar, the Seychelles, Comoros, Mauritius, and Reunion. In some of the countries of the sub-region, at least 80 percent of the population can be considered coastal. Overexploitation of coastal and marine resources and the degradation of the resource base could significantly limit the sub-region's potential for sustainable economic growth and development. In 1997, the Secretariat for Eastern African Coastal Area Management was launched in Maputo, Mozambique, to assist countries in the East African Region to coordinate and implement Integrated Coastal Management (ICM) activities. Capacity building and the need for enhanced information sharing were seen as critical issues. Critical skills that needed to be built up included techniques for problem solving, strategic planning, project/program monitoring and evaluation, and conflict resolution. In mid-1998, an Institutional Development Fund Grant for US$396,000 from the World Bank was provided for promoting Integrated Coastal Zone Management in the sub-region. Technical assistance, training, and equipment were provided to build capacity, particularly at the provincial and local levels where capacity is virtually non-existent. This Note summarizes the impact on the ground and the lessons learned from such implementation.